Extended-Range Luminescence Dating of Central and Eastern Amazonia Sandy Terrains - Rodrigues, Fernanda Costa G.; Porat, Naomi; Mineli, Thays Desiree; Del Río, Ian; Niyonzima, Pontien; Nogueira, Luciana; Pupim, Fabiano do Nascimento; Silva, Cleverson Guizan; Baker, Paul; Fritz, Sherilyn; Wahnfried, Ingo; Kiefer, Gustavo; et al. (Frontiers in Earth Science, 2022)
The Amazonia biome hosts upland closed and open vegetation ecosystems, in which the current biogeographical patterns relate to the evolution of the physical landscape. Therefore, understanding the origin and timing of the substrates supporting different ecosystems is indispensable for better comprehension of Amazonian biogeography. Here we used quartz optically stimulated luminescence (OSL) and thermally transferred optically stimulated luminescence (TT-OSL) for dating sandy substrates of closed and open vegetation environments in Central and Eastern Amazonia, from both outcrop and drill core samples (Autazes core: PBAT-15-43). These sandy substrates present ages ranging from 1 ka up to almost 2 Ma, that were primarily interpreted as depositional ages of fluvial terraces. Moreover, ages are discussed in terms of potential geomorphic processes leading to the formation of substrates, such as soil mixing and apparent age of quartz from the parent bedrock. The coupling between OSL and TT-OSL techniques allow us to date sedimentary deposits covering the whole Quaternary, which implies a new time window for the Amazonia history.